Pengaruh Word of Mouth, Citra Merek dan Gaya Hidup terhadap Keputusan Pembelian Produk Motor Honda di Jakarta - Rizka Fajrina S; Jalaludin Jalaludin (J-MAS (Jurnal Manajemen dan Sains), 2023)
Today's motorbikes can say a lot of meaningful things to society. Motorcycle manufacturers are required to introduce new technology every year to boost sales. With increasingly stringent business regulations due to competition, companies are forced to meet consumer needs in addition to being able to sell their products. Word of mouth, brand image, and lifestyle are some of the variables that might influence consumer decisions to buy. The method used in this research is quantitative. The results of this study are the influence of word of mouth (X1) on the purchase decision of Honda motorcycle products in Jakarta (Y), namely the calculated f value is greater than f table, f count 13.449> 2.47 from f table. The influence of brand image (X2) on the purchase decision of Honda motorcycle products in Jakarta (Y), namely the value of f count is greater than f table, f count is 61,601 > 2.47 from f table. The influence of lifestyle (X3) on the purchase decision of Honda motorcycle products in Jakarta (Y), namely the value of f count is greater than f table, f count is 53,769 > 2.69 from f table. The influence of word of mouth, brand image and lifestyle on the purchase decision of Honda motorcycle products in Jakarta (Y), namely the calculated f value is greater than f table.